Beneficial effects of preoperative superselective embolization on carotid body tumor surgery: A 13-year single-center experience - Li, Nan; Wan, Yuan; Chen, Wei; Yang, Jianyong; Chang, Guangqi; Huang, Yonghui (Frontiers in Oncology, 2022)
Purpose This study presented our 13-year experience managing patients with CBTs (carotid body tumors) and was aimed to investigate the impact of pre-TAE (preoperative transarterial embolization) on CBT surgical resection. Methods This retrospective study reviewed 169 surgically excised CBTs between May 2007 and October 2020. According to whether to carry out the pre-TAE, the patients were classified into the embolization (EG) (n = 130) and non-embolization groups (NEG) (n = 39). Tumor classification was based on Shamblin criteria and tumor size. The demographic data, clinical features, and intraoperative and postoperative information about the patients were retrieved and analyzed. Results The average tumor size was (43.49 vs. 35.44 mm, p = 0.04) for EG and NEG. The mean surgical time (195.48 vs. 205.64 mins, p = 0.62) and intraoperative BL (blood loss) (215.15 vs. 251.41 cc, p = 0.59) were less, but the incidence of revascularization required (29% vs. 33%, p = 0.62) and total complications (26% vs. 36%, p = 0.32) were lower in EG compared to NEG. Similarly, according to the subgroup analysis, no significant differences were detected in the surgical time, BL, adverse events (AEs), and the revascularization in EG when compared to NEG for type I (n = 5 vs. 7), II (n = 105 vs. 27), and III (n = 20 vs. 5), respectively except for the surgical duration in type III (p < 0.05). However, a significantly lower incidence of AEs (230.25 vs. 350 cc, p = 0.038) and a decline in BL (28.57% vs. 48.15%, p = 0.049) in EG were observed compared to those in NEG patients for large CBTs (≥ 30 mm as the cutoff point). No surgery-related mortality was observed during the follow-up. Conclusions CBTs can be surgically resected safely and effectively with a need for pre-TAE, which significantly decreases the overall BL and AEs for large lesions (≥ 30 mm).